Mental health of African asylum-seekers and refugees in Hong Kong: using the social determinants of health framework - William Chi Wai Wong; Sealing Cheung; Heidi Yin Hai Miu; Julie Chen; Kelley Ann Loper; Eleanor Holroyd (BMC, 2017)
Abstract Background Hong Kong is non-signatory to the 1951 Refugee Convention and its 1967 Protocol, and has no systematic domestic policies committed to the rights of asylum-seekers and refugees (ASRs). This creates a tenuous setting for African ASRs there. This study explored how mapped social determinates of health has impacted the mental health and wellbeing of African ASR's in Hong Kong. Methods A cross-sectional survey was carried out with 374 African ASRs. The survey comprised of: (a) socio-demographics; (b) health status; (c) health behaviours; and, (d) social experiences. Associations between social determinants of health and depression screen were explored and multivariable regression analysis was conducted. Results Majority of participants were 18-37 years old (79.7%), male (77.2%), single (66.4%) and educated (60.9% high school and above). Over a third (36.1%) screened positive for depression. Analyses revealed that living with family reduced the odds of a positive depression screen (OR = 0.25, 95%CI = 0.07-0.88). Those perceiving their health to be "Poor" were 5.78 times as likely to be screened for depression. Additionally, those with higher scores on the discrimination scale were more likely to have positive depression screen (OR = 1.17, 95%CI = 1.10-1.24). Conclusion A significant proportion of African ASRs in Hong Kong exhibits depressive symptoms. A complex interaction combining both social and perceptions of health and discrimination in the host society is likely exacerbated by their ASR status. The use of community support groups or even re-examination of the family reunification laws could improve the mental health and wellbeing of African ASRs in Hong Kong.